2002
DOI: 10.1002/jbm.b.10526
|View full text |Cite
|
Sign up to set email alerts
|

In vitro corrosion testing of modular hip tapers

Abstract: The in vivo fretting behavior of modular hip prostheses was simulated to determine the effects of material combination and a unique TiN/AlN coating on fretting and corrosion at the taper interface. Fretting current, open-circuit potential (OCP), and quantities of soluble debris were measured to determine the role of mechanically assisted crevice corrosion on fretting and corrosion of modular hip tapers. Test groups consisting of similar-alloy (Co-Cr-Mo head/Co-Cr-Mo neck), mixed-alloy (Co-Cr-Mo head/Ti-6Al-4V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
140
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 29 publications
11
140
0
3
Order By: Relevance
“…Subsequently, they investigated the behavior of a modular head/ neck assembly in which the neck was coated with a TiN-AlN coating. 8 Coated samples had a higher resistance to fretting corrosion within the load range tested (0-3,200 N), as demonstrated by significantly decreased fretting currents compared to those with uncoated mixed alloy couples.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Subsequently, they investigated the behavior of a modular head/ neck assembly in which the neck was coated with a TiN-AlN coating. 8 Coated samples had a higher resistance to fretting corrosion within the load range tested (0-3,200 N), as demonstrated by significantly decreased fretting currents compared to those with uncoated mixed alloy couples.…”
Section: Introductionmentioning
confidence: 84%
“…8 OCP measurements were made using a saturated calomel electrode (SCE; Accumet, Fisher Scientific, Pittsburgh, PA) connected to a high impedance electrometer (Model 6514, Keithley Instruments, Cleveland, OH). Fretting current measurements were made using a cylindrical counter electrode connected to a zeroresistance ammeter (Model 6485, Keithley Instruments).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and finite element studies have shown that fretting would occur from micromotion at the interface [14,15,22,25]. Retrieval studies have documented corrosion of the headneck interface secondary to fretting [5,16,18,23].…”
Section: Discussionmentioning
confidence: 99%
“…Complications of this modular junction include fretting [6-8, 12, 16, 23], crevice corrosion [6-8, 12, 13, 16, 23], and fracture of the trunnion [2,4,13,15,19,28]. The most common reason for revision of a unipolar endoprosthesis is stem loosening [1,10,27] or acetabular erosion from the large femoral head articulating on the host acetabular cartilage and not from complications of the trunnion [10,17,24,26,27].…”
Section: Introductionmentioning
confidence: 99%